2023
DOI: 10.1037/ser0000627
|View full text |Cite
|
Sign up to set email alerts
|

Social support over time for men and women veterans with and without complex trauma histories.

Abstract: Social support is closely linked to health, but little is known about United States (U.S.) veterans' social support over time and factors that may influence their support trajectories. This study investigates social support over time for U.S. men and women Post-9/11 veterans in relation to trauma history and gender. A secondary analysis of longitudinal cohort data from the Survey of Experiences of Returning Veterans (SERV), which employed a repeated-measures longitudinal design using five waves of data (baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
3
0
1
Order By: Relevance
“…Social support is a multifaceted construct, widely recognized as a predictor of physical, mental, and social well‐being (Benda, 2006; Hale Ma et al, 2005; Hwang et al, 2009; Taylor, 2018; VandenBos, 2015) and having remarkable stability over time (Scoglio et al, 2023). Social support may include any persons or settings in one's community that provide comfort or assistance, including informal networks, such as interpersonal relationships and community connection, and formal networks, such as places of worship, educational institutions, and other community agencies (Benda, 2006; Herrenkohl et al, 2016; Hwang et al, 2009; Taylor, 2018; VandenBos, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Social support is a multifaceted construct, widely recognized as a predictor of physical, mental, and social well‐being (Benda, 2006; Hale Ma et al, 2005; Hwang et al, 2009; Taylor, 2018; VandenBos, 2015) and having remarkable stability over time (Scoglio et al, 2023). Social support may include any persons or settings in one's community that provide comfort or assistance, including informal networks, such as interpersonal relationships and community connection, and formal networks, such as places of worship, educational institutions, and other community agencies (Benda, 2006; Herrenkohl et al, 2016; Hwang et al, 2009; Taylor, 2018; VandenBos, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…ISSN (Digital): 2223-7666 Liberabit, 2024, 30(1), e743 (enero -junio) En relación con el apoyo social percibido (ASP), se conceptualiza como la disponibilidad de recursos y conexiones sociales que presenta una persona (Scoglio et al, 2023); además, se caracteriza por el apoyo emocional (cuidado e intimidad), informativo (orientación) e instrumental (ayuda directa y servicios) que proviene de fuentes significativas (familia o amigos) y le brindan seguridad al individuo (Scardera et al, 2020). De igual manera, permite mitigar los efectos negativos de las situaciones adversas, potencia los recursos de afrontamiento (Zhao & Wang, 2023) y tiende a relacionarse con el bienestar psicológico (Zarate et al, 2022).…”
Section: Introductionunclassified
“…For example, received and/or perceived social support from specific sources, such as veteran friends, may be particularly important for veterans given shared experiences and traumas that nonveterans may have a harder time relating to (e.g., combat, military sexual trauma). Among veterans who served after post-9/11, Scoglio et al (2023) found that across a 12-month period, social support (i.e., emotional sustenance and instrumental assistance) was significantly associated with the severity of posttraumatic symptoms and SI. Of note, as Scoglio et al (2023) did not identify gender as a significant predictor of postmilitary social support, it was not included in their multivariate regression models.…”
mentioning
confidence: 96%
“…Among veterans who served after post-9/11, Scoglio et al (2023) found that across a 12-month period, social support (i.e., emotional sustenance and instrumental assistance) was significantly associated with the severity of posttraumatic symptoms and SI. Of note, as Scoglio et al (2023) did not identify gender as a significant predictor of postmilitary social support, it was not included in their multivariate regression models. Conversely, in another study of Gulf War I era veterans, Vogt et al (2005) found that perceived unit social support during deployment was more protective against mental health consequences for women than men veterans.…”
mentioning
confidence: 96%